2019
DOI: 10.1002/crat.201900002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Strontium Ions on Crystallization of Amorphous Calcium Carbonate

Abstract: In biomineralization, amorphous precursors enable formation of complicated crystal shapes and incorporation of organic and inorganic impurities. In some cases the concentrations of the inorganic impurity atoms greatly exceed the thermodynamical (equilibrium) solubility limits. To shed additional light on this, crystallization experiments with Sr-rich amorphous calcium carbonate (ACC) are carried out. The Sr-concentration in ACC, Sr/(Ca+Sr) 0.3, is more than 60 times larger than its solubility limit in calcite.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…[ 3 ] In some organisms ACC can be stabilized for many years. [ 4 ] Previous studies have shown that the high stability of biogenic ACC could be attributed to the presence of soluble inorganic and organic additives, such as magnesium (Mg 2+ ) ions, [ 5 ] strontium (Sr 2+ ) ions, [ 6 ] silicate (SiO 4 4− ) ions, [ 7 ] phosphate (PO 4 3− ) ions, [ 4,8 ] organic molecules, [ 9 ] phosphorylated proteins, [ 8a ] and intrinsically disordered proteins, [ 10 ] etc. Because crystallization of ACC in solution typically proceeds via a dissolution and recrystallization mechanism, [ 11 ] the high stability of ACC in the presence of additives is often ascribed to their ability to inhibit the dissolution of ACC or the formation of crystalline phases.…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 ] In some organisms ACC can be stabilized for many years. [ 4 ] Previous studies have shown that the high stability of biogenic ACC could be attributed to the presence of soluble inorganic and organic additives, such as magnesium (Mg 2+ ) ions, [ 5 ] strontium (Sr 2+ ) ions, [ 6 ] silicate (SiO 4 4− ) ions, [ 7 ] phosphate (PO 4 3− ) ions, [ 4,8 ] organic molecules, [ 9 ] phosphorylated proteins, [ 8a ] and intrinsically disordered proteins, [ 10 ] etc. Because crystallization of ACC in solution typically proceeds via a dissolution and recrystallization mechanism, [ 11 ] the high stability of ACC in the presence of additives is often ascribed to their ability to inhibit the dissolution of ACC or the formation of crystalline phases.…”
Section: Introductionmentioning
confidence: 99%
“…In both Fig.6 a) and b), the composition was checked with EDX (Section 11 in the Supplementary Information), confirming that the species at the surfaces contain Sr and O (but no Ag or Fe). The amorphous form of the carbonate and hydroxide is possible[31,32], although neither is thermally stable. In contrast, the surface of the sample calcined at 650ºC, Fig.6 c) and d), was free of impurities.…”
mentioning
confidence: 99%
“…For the initial systems, 50–200 additive ions were replaced by Ca 2+ ions (e.g., x = 0.25, 0.5, 0.75, and 1.0). Note that these high fractions of additive ions (i.e., x ≥ 0.25) have been reported to be experimentally feasible in the previous literature. ,, Next, according to the previously reported dehydration scheme by Wallace et al, we removed water molecules until the water-to-cation ratio ( n ) became zero. It was achieved through a total of 18 sequential NPT MD simulations; each simulation contained 200 (i.e., H 2 O/Ca 2+ ratio = ∼2–9) or 40 (i.e., H 2 O/Ca 2+ ratio = ∼0–2) fewer water molecules than the previous step.…”
Section: Methodsmentioning
confidence: 99%